Pengendalian Banjir di kawasan Sempadan Sungai Kali Lamong Kabupaten Gresik Melalui Pembangunan Tanggul - Romadhan, Ach. Apriyanto; Fakhri, Ahmad Rusydan; Sihidi, Iradhad Taqwa (JPAP: Jurnal Penelitian Administrasi Publik, 2023)
This paper explains how flood control is carried out in the Kali Lamong river basin area, Gresik Regency, to overcome flood disasters through the construction of dams. To answer this question, this paper uses the policy implementation theory from Edwards III and a qualitative descriptive research method with data collection through interviews, observation, and documentation. Research shows that the implementation has been realized, both seen from the communication carried out by the Great River Basin Office (BBWS) through the initial stages of communication, the implementation of the socialization of flood control patterns, the implementation of embankment construction, compensation to monthly evaluations to monitor the implementation of policies, as well as competent appropriate resources. in carrying out their duties, a supportive bureaucratic structure and a clear non-overlapping division of authority carried out by BBWS Bengawan Solo so that the implementation of the policy is carried out properly and is free from the annual flood disaster since 2013. Apart from theoretically this research looks at the extent to which the implementation of the policy Flood control carried out by BBWS Bengawan Solo is carried out to reduce the impact of flooding in Gresik Regency through the construction of a dam.